Community opinion on the personal brand of Bobby Nasution to Prospective Medan Mayor in 2020 - Panjaitan, Fathur Rahman; Harahap, Muhammad Said (Universitas Ahmad Dahlan, 2021)
The current phenomenon in the world of politics is flooded with families of politicians who run for politics. Where the next cabinet will be dominated by young people. On the other hand, a young politician, although included in the scope of a political dynasty, shows that young people are not politically apathetic. And to continue to exist in the world of politics, personal branding is needed where every candidate for politicians must build a name or reputation which means creating a